Porphyromonas gingivalis gingipain is involved in the detachment and aggregation of Aggregatibacter actinomycetemcomitans biofilm. (10th April 2014) - Haraguchi, A.; Miura, M.; Fujise, O.; Hamachi, T.; Nishimura, F.
Summary Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are major periodontal pathogens that cause several types of periodontal disease. Our previous study suggested that P. gingivalis gingipains secreted in the subgingival environment are related to the detachment of A.actinomycetemcomitans biofilms. However, it remains unclear whether arginine‐specific cysteine proteinase (Rgp) and lysine‐specific proteinase (Kgp) play different roles in the detachment of A. actinomycetemcomitans biofilm. The aim of this study was to investigate possible disruptive roles of Kgp and Rgp in the aggregation and attachment of A. actinomycetemcomitans. While P. gingivalis ATCC33277 culture supernatant has an ability to decrease autoaggregation and coaggregation of A. actinomycetemcomitans cells, neither the boiled culture supernatant of ATCC33277 nor the culture supernatant of KDP136 showed this ability. The addition of KYT‐1 and KYT‐36, specific inhibitors of Rgp and Kgp, respectively, showed no influence on the ability of P. gingivalis culture supernatant. The result of gelatin zymography suggested that other proteases processed by gingipains mediated the decrease of A. actinomycetemcomitans aggregations. We also examined the biofilm‐destructive effect of gingipains by assessing the detachment of A. actinomycetemcomitans from polystyrene surfaces. Scanning electron microscope analysis indicated that A. actinomycetemcomitans cells were detached by P. gingivalis Kgp. The quantity of A. actinomycetemcomitans in biofilm was decreased in co‐culture with P. gingivalis. However, this was not found after the addition of KYT‐36. These findings suggest that Kgp is a critical component for the detachment and decrease of A. actinomycetemcomitans biofilms.